Development and evaluation of effects of Internet-based tutorial module framed by Cognitive Apprenticeship Model for statistics learning among Malaysian postgraduate students - Saadati, Farzaneh (2014)
This dissertation illustrates the development of an Internet-based tutorial module (i-TModule) framed with Cognitive Apprenticeship Model (CAM) and employing the systematic instructional design process, known as Analysis, Design, Development,Implementation, and Evaluation (ADDIE). This module has utilized a Learning Management System (LMS) to develop the tutoring environment by incorporating: a) the use of the Internet-based resources in varying formats (video, text, animation,charts, etc), b) the utilisation of engaged learning activities during “odd hours” in an effort to improve the students’ mathematical achievement and problem solving skills,c) individualized the students’ learning experiences by altering some subsequent instructional contents and activities based on CAM according to individual needs, and d) monitoring and assessing of individual problem-solving skills, online behaviour,and reaction during the delivery of the designed instruction. The first phase of the study focused on conducting run-through analyses of the target group’s needs, designing the learning strategies, and developing the learning assessments and activities. The major goal of this phase was to achieve a flexible and dynamic Moodle-based constructivism environment, the i-TModule, based on CAM as a framework during the instructional process. The second phase focused on evaluating the effectiveness of the designed instruction using learners’ performance on statistics tests, problem-solving skills, online behaviour, online reaction, and motivation towards learning as indicators among the postgraduate students. The effects of the i-TModule (facilitated using the CAM) versus the conventional Moodle-based module (not facilitated by CAM) were compared using the above-mentioned indicators. Two groups of postgraduate students who enrolled in Educational Statistics course in one of the faculty in UPM during 2012-2013, were participant of this study. The first group received treatment by using i-TModule while the following cohort group was given the conventional Moodlebased module. A pretest-posttest statistical analysis was also conducted to evaluate the effects of the i-TModule on statistics performance. The result of this study showed that the use of i-TModule has a significant effect on students’ statistics performance in three tests as well as their motivation toward learning. The results also clearly indicated that the developed module provided a motivating context and learning environment which could capture the interest of learners (attention), meet their personal needs (relevance), help them to believe and control success (confidence), and allow them to have good experiences (satisfaction). Furthermore, these results indicated that the delivery system based on CAM has significantly enhanced students’ performance in their statistics problem-solving skills. Likewise, the study showed i-TModule has influenced changes (statistically significant changes) of online behaviour and reaction among students across the 14 weeks learning sessions. In addition, the capability of Moodle was confirmed as a teaching and learning medium in the current technological context. The results were the identification of a value added teaching and learning strategy with salient features of CAM which was able to supplement a face-to-face instruction. The developed module had incorporated into the instructional strategy and constructively supported all learning activities and assessments tasks. It also demonstrated the potential of Moodle as a web-based learning platform and confirmed the place for CAM features within the area of learning, specifically Educational Statistics among postgraduate students.